Gampong Implementation of School Accreditation in Improving the Quality of Education in SD Negeri Jawa - Muttakin; Widya; Riza Andriani; Amam Taufiq Hidayat; Mice Putri Afriyani; Bakhtiar (PT FORMOSA CENDEKIA GLOBAL, 2022)
SD Negeri Gampong Jawa is one of the elementary schools in Langsa City, Aceh. SD Negeri Gampong Jawa has completed a series of re-accreditation activities, from meeting the requirements to filling in the accreditation instruments and field assessments. This Community Service activity is a field assessment for accreditation activities at SD Negeri Gampong Jawa, Lhokseumawe City. The results of school accreditation include four components: quality of graduates, learning process, teacher quality, and school management. Based on the assessment results, information was obtained that SD Negeri Gampong Jawa applied good quality standards for the four components above. Then, the assessor provides recommendations to the school principal for continuous improvement of the school. The Head of Gampong Public Elementary School accepts the recommendations given well and is committed to implementing them in the future.